The Effect of Income, Health Level, and Education Levels on the Welfare of Palm Oil Farmers: A Case Study of Riau Province - Rahmah, Nadya Aulia; Cupian, Cupian; Amar, Siti Chaerani Djen (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the effect of income level, health level, and education level on the welfare of palm oil farmers in Riau Province. The research uses a quantitative descriptive approach. Data were collected through questionnaires distributed to 56 smallholder farmers in Riau Province. The results show that income, health, and education variables significantly affect farmers’ welfare. Higher household income, access to health insurance, and education level substantially improve farmers’ living standards. Therefore, the study emphasizes the importance of government policies to enhance economic, health, and educational access for rural communities.